Daumier : visions of Paris ; [first published on the occasion of the Exhibition "Daumier (1808 - 1879): Visions of Paris", Royal Academy of Arts, London, 26 October 2013 - 26 January 2014] - Daumier, Honoré (Royal Academy of Arts, 2013)
Honore Daumier (1808-1879) is perhaps best known for his political and social caricatures, precise and witty observations of life in nineteenth-century France. This authoritative new study provides a long-overdue assessment of his entire oeuvre, bringing together his paintings, sculptures, watercolours, drawings and lithographs, all of which were greatly admired in his lifetime. Later feted by Van Gogh and Picasso, Daumiers art continues to be appreciated by such contemporary artists as Paula Rego and Peter Doig